The role of sports mega-events in China's unique soft power strategy. - Jeong, Joonoh; Grix, Jonathan; Grix, Louis (Humanities & Social Sciences Communications, 2024)
This article investigates the contribution of states' soft power strategies to the process of East Asia's increasing global economic and political significance. We identify hosting sports mega-events as key to such strategies and thereby seek to add to both the literature on regional 'soft power' and acquiring it through sport. Using East Asia as the focus, we concentrate on China's leveraging of the Beijing 2008 and 2022 Olympics for soft power gains. We show that China's propaganda system is also part of their soft power strategy, which tends to focus primarily on domestic soft power. Our findings indicate that China cares about its national image abroad but places greater emphasis on attaining domestic soft power. Knowing that China's understanding of 'soft power' is distinctly different from the 'West' allows greater insight into their approach to regional and international soft power acquisition.